Development of a Practical/Industrial Training Automated System (PITAS) in the management of information / Siti Nursarjana Malim, Azlina Bujang and Mohammad Zamri Abd Rahim - Malim, Siti Nursarjana; Bujang, Azlina; Abd Rahim, Mohammad Zamri (Research Management Institute (RMI), 2013)
The aim of this research is to discuss the students' perceptions towards the implementation of automated system to help the organization to manage records and documents. The number of students who registers for practical/industrial training has increased every semester, therefore the amount of data to be recorded has also increased. In the search of systematic and cost effective ways of managing the information, there is a need to overcome the problem of filling the system manually. In consequence, this study would examine whether the development of automation system has significantly made the data management more efficient and effective (data collection, data storage and data retrieval). From the evaluation, students' perceptions towards its implementation were analysed where 200 questionnaires were distributed among students of various programmes in Universiti Teknologi MARA Sarawak. The returned questionnaires were then analyzed using SPSS (Version 17). From the findings, it can be concluded that the implementation of such application could really contribute to the improvement of the information resources of the practical/industrial attachment students. This further ensures that the connection between the practical training coordinator and the students is uninterrupted. Apart from that, a good industrial relationship (between the management and organisation) can also be established. The research outcome indicated positive perceptions and responses from the students regarding the development of the application. Thus, the implementation of the proposed system should be considered to be used continuously as an automated information delivery tool.